STRATEGY OF PARENTS IN ASSISTANCE OF STUDENTS LEARNING SUBJECTS OF BUDDHIST RELIGIOUS EDUCATION AND PRACTICES AT PAIT 02 SDN 02 DURING THE COVID-19 PANDEMIC - Mariani, Cica (Jurnal Pencerahan, 2022)
One of the impacts of the Covid-19 pandemic on the education sector is changing the face-to-face learning system into online learning. During the COVID-19 pandemic season, teaching and learning is carried out online or online. In the online teaching and learning process, usually parents are often faced with various problems. In addition to health problems, parents have faced many problems in their children's education during the pandemic. Distance learning causes them to be the main teachers of children who are still in elementary school. The learning process for Buddhism and character education during the COVID-19 pandemic is carried out online or online. In this study the research method used is descriptive qualitative research method and data collection using snowball sampling. In this study, it was found that parents who when their children cannot focus on learning they reprimand directly so that children can have concentration again. Besides that, parents also open the internet to help their children's learning